PENGARUH MODAL DAN LAMA JAM KERJATERHADAP TINGKAT PENDAPATAN PEDAGANG KAKI LIMA - berchman prana sasmita; Gunawan Sudarmanto; Tedi Rusman (FKIP Unila, 2013)
The purpose of this study was to know the influence of capital and outpouring of work time towards the level of income of cadgeron market technical implementing at Gadingrejo in 2012/2013. The population of this research was street vendors in Gadingrejo’s market with 138 traders number. By using T.Yamane formula, founded the samples as many as 102 traders. The methodology of this research was descriptive correlationally andthe regression was conducted to analysis data.Result of this research, indicated that: (1) there is a positive and significant influence of working capital towards the level of income of cadger on market technical implementing at Gadingrejo’s market in 2012/2013, (2) there is a positive and significant influence of outpouring of work time towards the level of income of cadgeron market technical implementing at Gadingrejo’s market in 2012/2013, (3) there is a positive and significant influence of capital outpouring of work time on the level of incomeof cadgeron market technical implementing at Gadingrejo’s market in 2012/2013.Keywords: Capital, Outpouring of work time andincome levels